2014
DOI: 10.1111/1365-2435.12361
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive acceleration in growth and development of salamander hatchlings in cannibalistic situations

Abstract: Summary 1.In most animal species, the hatchling stage is a highly vulnerable life-history stage. In many fish and amphibian species, hatchling abundance varies substantially among sites and years, with the result that selection strength in conspecific interactions such as cannibalism is also variable. The variability of selection leads species to evolve phenotypic plasticity, and adaptive trait changes in hatchlings that depend on the density of conspecifics can therefore be expected. However, plasticity strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…In Experiment 3, we found that H. retardatus salamander larvae were 83% more likely than R. pirica frog tadpoles to attack and consume the accessible toad hatchling (Result 3.1.1). This is reasonable considering that H. retardatus salamander larvae specialise in consuming amphibian larvae (Kishida, Tezuka, Ikeda, Takatsu, & Michimae, 2015;Kishida, Trussell, & Nishimura, 2009;Wakahara, 1995;Yamaguchi, Takatsu, & Kishida, 2016), in contrast to the opportunistic R. pirica frog tadpoles. Nevertheless, we found that the consumption rate of frog tadpoles was 338% greater than that of salamander larvae in the aquarium experiment (Experiment 2, .…”
Section: Discussionmentioning
confidence: 75%
“…In Experiment 3, we found that H. retardatus salamander larvae were 83% more likely than R. pirica frog tadpoles to attack and consume the accessible toad hatchling (Result 3.1.1). This is reasonable considering that H. retardatus salamander larvae specialise in consuming amphibian larvae (Kishida, Tezuka, Ikeda, Takatsu, & Michimae, 2015;Kishida, Trussell, & Nishimura, 2009;Wakahara, 1995;Yamaguchi, Takatsu, & Kishida, 2016), in contrast to the opportunistic R. pirica frog tadpoles. Nevertheless, we found that the consumption rate of frog tadpoles was 338% greater than that of salamander larvae in the aquarium experiment (Experiment 2, .…”
Section: Discussionmentioning
confidence: 75%
“…Although most frequently studied in marine organisms (Oyarzun and Strathmann 2011), a pre‐feeding larval period also occurs in many amphibians, and may also be targeted by stage‐specific threats. These larvae can be extremely vulnerable immediately after their emergence from the protective egg capsule due to their small size, limited defenses, and low motility (Kishida et al 2015). Pre‐feeding larvae can respond to environmental cues, including cannibalism (Kishida et al 2015) and food limitation (Adams et al 2011), and such responses can negatively affect subsequent performance (Marshall et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The size advantage might also result in predation by the early‐hatched individuals on the smaller individuals that hatched later. Such predation at the intraspecific level, that is cannibalism, has the potential to affect the survival, development and growth of individuals in a population (Eitam et al., ; Hopper, Crowley, & Kielman, ; Kishida, Tezuka, Ikeda, Takatsu, & Michimae, ). At the population level, cannibalism results in a more even size distribution and tends to stabilize population dynamics (Claessen, De Roos, & Persson, ).…”
Section: Introductionmentioning
confidence: 99%